If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -15x + -6 + -45x + 25 + -25x = 0 Reorder the terms: 15 + -6 + 25 + -15x + -45x + -25x = 0 Combine like terms: 15 + -6 = 9 9 + 25 + -15x + -45x + -25x = 0 Combine like terms: 9 + 25 = 34 34 + -15x + -45x + -25x = 0 Combine like terms: -15x + -45x = -60x 34 + -60x + -25x = 0 Combine like terms: -60x + -25x = -85x 34 + -85x = 0 Solving 34 + -85x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + -85x = 0 + -34 Combine like terms: 34 + -34 = 0 0 + -85x = 0 + -34 -85x = 0 + -34 Combine like terms: 0 + -34 = -34 -85x = -34 Divide each side by '-85'. x = 0.4 Simplifying x = 0.4
| 0.03(7t-9)=0.21(t-5)+0.78 | | 13+3g=2g | | 9=v-7 | | x^2-(76.01)x+9.24=0 | | -90=5(3x-6) | | 3p-28-p=7+10p-10 | | 35=14-7a | | -16j-4=-12j-16 | | 7dag= | | m^4+5m^2-36=0 | | 3a+2b+4c=75 | | 6x+3+4+2x-x+8=79 | | 12cg= | | -372=12(-12+x) | | 18+6z=-6 | | -3y+27=4(y-9) | | 7+2y=13 | | 4x^2-1x-72=0 | | 10c+9=11 | | 2(h-2)-h=h-4 | | x(x+1)=3 | | 3x+9=12x+81 | | -7(v+3)=-5v-35 | | 0.2x+4.9=0.9x-0.7 | | f(3t)=3x^2-2 | | -30n=-27n+28 | | 2-m=6m-12 | | 4a+3b+2c=75 | | -7u+20=-2(u+5) | | 10x-6=2x+42 | | F(x)=c^3+5c-8 | | 3y+3(y-8)=6 |